(untitled) (Jagannath University Journal of Science, 2025)
In financial market, option pricing plays a vital role in the stock market and having significant outlook in the economic development of a nation. In business and stock market, different financial models are developed for computing options for stocks or bonds. In this work, we focused on basic concepts of trinomial tree model, derivation and algorithm and application of it. Here, we apply the trinomial model for American and European option pricing. Basically, we applied the techniques to obtain American and European option prices to incorporate an investor’s view of the future behavior of the stock market related to European and American options. Finally, we showed some basic difference between American and European option applying trinomial model. Jagannath University Journal of Science, Volume 11, Number 2, Dec. 2024, pp. 45−57